2003
DOI: 10.1021/ac0350918
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Sensor for General Purpose Organohalide Detection at Picogram per Liter Concentrations Based on a Simple Collector−Generator Method

Abstract: With the aim of producing a general purpose sensor for environmental analysis, we describe a simple and sensitive method for organohalide detection, based on an electrochemical collector-generator process. The sensor consists of four coplanar electrodes contacting a solution volume of 300 microL, containing organohalide. At the first working electrode (a Zn/PTFE composite), the analyte is electrolyzed to liberate halide ions. At the second working electrode (Ag), the halide ions are detected by cathodic stripp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Dobson et al [185] indicated that haloalkanes have a limit of detection of 5 µM at porphyrin-modified electrodes. To date, one of the most sensitive sensors for organohalides is a zinc metal-polytetrafluoroethylene particle (PTFE) composite-plated electrode, with a detection limit of 0.1 nM, that was designed by Wiyaratn and co-workers [186][187][188]. In our own investigation [174] of the determination of THMs in drinking water by means of stripping analysis with silver electrodes, detection limits of 3.0 µg L -1 (12 nM) and 6.0 µg L -1 (50 nM) for bromoform and chloroform, respectively, were achieved.…”
Section: Detection Of Thms and Haasmentioning
confidence: 99%
“…Dobson et al [185] indicated that haloalkanes have a limit of detection of 5 µM at porphyrin-modified electrodes. To date, one of the most sensitive sensors for organohalides is a zinc metal-polytetrafluoroethylene particle (PTFE) composite-plated electrode, with a detection limit of 0.1 nM, that was designed by Wiyaratn and co-workers [186][187][188]. In our own investigation [174] of the determination of THMs in drinking water by means of stripping analysis with silver electrodes, detection limits of 3.0 µg L -1 (12 nM) and 6.0 µg L -1 (50 nM) for bromoform and chloroform, respectively, were achieved.…”
Section: Detection Of Thms and Haasmentioning
confidence: 99%
“…Wiyaratn et al described a simple but highly sensitive electrochemical collector-generator process to detect organohalides with a 0.1 nM detection limit. 73 Analyte electrolysis and release of halide ions was achieved at a first Zn/PTFE composite working electrode, followed by the detection of the released halides at a second silver working electrode by cathodic stripping voltammetry. The continuous collection of electrolysis product at the second electrode for a period of 600-s was responsible for the low detection limit.…”
Section: Voltammetric Sensors: Spectroelectrochemical Sensors Couplementioning
confidence: 99%
“…Electrochemical techniques have been proposed as a promising method for the measurement of environmental pollutants due to their fast, simple and inexpensive equipment [10,11]. The oxidation of tetracycline (TC) has been reported by gold [12], ruthenium oxide-hexacyanoruthenate (RuO-RuCN) [13] or multiwall carbon nanotubes (MWNTs) [14] modified electrodes.…”
Section: Introductionmentioning
confidence: 99%